Diseño de máquina desvainadora de alverja con capacidad de 500 kg/día (2024)
This project develops the design of a pea shelling machine as a technologically advanced alternative for shelling dry pea shells. The project begins with the analysis of technologies presented on pea shelling and reference machines that use shelling systems in legume-type foods. At this stage the selection of the shelling system is carried out through two (2) axes obtained in the design requirements and the different variables such as dimensions, machine structure, power, torque and other systems that ensure the correct functioning of the machine. Carrying out the relevant calculations for each element used in the project.